On some aspects of studying the topic «Russia: trials and heroes» within the framework of the discipline «Fundamentals of Russian Statehood» - V. V. Volkov; M. V. Mаryeva (Вестник Майкопского государственного технологического университета)
The article considers the issue of teaching the new course «Fundamentals of Russian Statehood», which has been introduced everywhere into the programs of universities in the country only since 2023, which determines its relevance. The authors are trying to solve the problem: how to awaken a sense of patriotism in young people, convey to them the values of Russian civilization and do this in a way that does not cause rejection or resistance?The goal of the research is to find a theoretical and methodological basis for sensitive, but at the same time effective teaching of the discipline «Fundamentals of Russian Statehood» and to demonstrate the chosen pedagogical strategy using the example of studying the topic «Russia: Trials and Heroes».The authors of the article, using methods of semantic and structural analysis, have formed an ideological framework and set the logic for selecting material, which allows them to provide the necessary information within the chosen topic in a targeted and orderly manner.The result of the research was methodological recommendations and materials for studying the topic «Russia: trials and heroes». In order to avoid a moralizing tone and excessive pathos, it has been proposed to adhere to such pedagogical principles and techniques as focusing on dialogue, relying on previously formed knowledge and ideas, searching for connections between this topic and modernity and professional interests that are relevant for certain groups of students.The Conclusions. The article has a clear practical focus. It presents methodological developments, including, among other things, a logically structured plan and specific tasks on the topic «Russia: trials and heroes».